Methodology To Determine Photovoltaic Inverter Conversion Efficiency For The Equatorial Region - Ab Rahman, Azhan; Salam, Zainal; Shaari, Sulaiman; Ramli, Mohd zulkifli (MDPI AG, 2020)
Photovoltaic inverter conversion efficiency is closely related to the energy yield of a photovoltaic system. Usually, the peak efficiency (ηmax) value from the inverter data sheet is used, but it is inaccurate because the inverter rarely operates at the peak power. The weighted efficiency is a preferable alternative as it inherently considers the power conversion characteristics of the inverter when subjected to varying irradiance. However, since the weighted efficiency is influenced by irradiance, its value may not be appropriate for different climatic conditions. Based on this premise, this work investigates the non-suitability of the European weighted efficiency (ηEURO) for inverters installed in the Equatorial region. It utilizes a one year data from the Equatorial irradiance profile to recalculate the value of ηEURO (ηEURO_recal) and to compare it with the original ηEURO. Furthermore, a new weighted efficiency formula for the Equatorial climate (ηEQUA) is proposed. Validation results showed that calculated energy yield with ηEQUA closely matched the real energy yield of 3 kW system with only 0.16% difference. It is envisaged that the usage of ηEQUA instead of ηmax or ηEURO will results in a more accurate energy yield and return of investment calculations for PV systems installed in Equatorial regions.